Transformation of Character Assessment through ICT Technology: A Study of the Use of Web-Based Platforms - Saputra, Andi; Musonda, Allan; Nikolantonakis, Kostas (jurnal matematika, 2024)
Purpose of the study: The purpose of this study was to determine the perceptions of teachers, students, and parents towards the use of a web-based character assessment system supported by Information and Communication Technology (ICT), and to determine the results of student character using a web-based character assessment system. Methodology: This study uses a quantitative research approach with a descriptive design. The tools used include a perception questionnaire and a web-based character assessment system. Data were collected using a questionnaire for perception data, and character data were collected using a web-based platform for character assessment. Analysis was performed using SPSS for descriptive statistical evaluation. Main Findings: The study found that the majority of teachers (70%), students (68.67%), and parents (76%) rated the web-based character assessment system as very effective. The results showed that most students achieved good or excellent character outcomes, with an average score of 70.0. This demonstrates the system's ability to accurately assess and support students' character development. Novelty/Originality of this study: This study introduces a comprehensive, ICT-enabled, web-based character assessment model that combines real-time data, transparency, and collaboration between schools and families. This study advances existing knowledge by demonstrating the potential of technology to enhance character education, providing a scalable framework for broader educational applications.